Jean des Murs’s Canones tabularum Alfonsii of 1339 - Nothaft, CPE (Brill Online, 2019)
Among the works by Jean des Murs that have yet to be printed are his Canones tabularum Alfonsii, which he wrote in 1339 during his last attested stay at the Collège de Sorbonne. One element of particular interest in this concisely worded text is Jean’s discussion of the length of the solar year, which was the first to take into consideration the consequences of the Alfonsine precession model for the length of the tropical year. Another is his approach to finding the time of true syzygy, which can be compared with some of his earlier writings on the same topic. Taken together, these writings reveal something about Jean’s development as an astronomer over time, as he adjusted his preferred method of syzygy computation in reaction to empirical data. The article concludes with a look at the chapters devoted to the calculation of eclipse times and magnitudes, which turn out to be strongly influenced by John of Genoa’s Canones eclipsium, written in 1332.